Terrorism and counterterrorism - Nacos, Brigitte L. (Pearson, 2012)
Focusing on the phenomenon of terrorism in the post-9/11 era, Terrorism and Counterterrorism investigates this form of political violence in an international and American context and in light of new and historical trends. In this comprehensive and highly readable book, Brigitte Nacos, a renowned expert in the field, clearly defines terrorism's diverse causes, actors, and strategies, outlines anti- and counter-terrorist responses, and highlights terrorism's relationship with the media and the public.